Sliding mode control of shifting process based on throttle opening and vehicle mass variations. (2015) - Luo, Peipei; Hu, Yuhui; Nie, Xingfu; Xi, Junqiang
In order to reduce the friction work in the inertial phase of shifting process of heavy-duty vehicle (HDV), a complete vehicle model and a shifting process model are built firstly to analyse the dynamical character of automatic transmission (AT)'s shifting process. Then, throttle opening and vehicle mass are introduced as modification in the inertial phase control, and the friction elements' speed difference is treated as control objective. A sliding mode control (SMC) is adapted to realise this control, and shows a better target tracing feature than the conventional PID control. The results of real vehicle test verify the proposed control strategy, and the vehicle has a good shifting behaviour.